ENGLISH PRIMARY SCHOOL TEACHERS’ PERCEPTIONS AND IMPLEMENTATION OF PEDAGOGICAL CONTENT KNOWLEDGE IN GIANYAR - L.P. Krissiana Permata Dewi; I G A Lokita Purnamika Utami; K. Sintya Dewi (Jurnal IKA, 2020)
This study aimed at describing the primary school English teachers’ perceptions and implementation of pedagogical content knowledge (PCK) of teaching English for young learners (TEYL), as well as the consistency between the perceptions and implementation of PCK in TEYL, especially in Gianyar. This study involved 2 primary school English teachers from 2 different schools in Gianyar which were selected by using convenience sampling. The research design used was embedded mixed method which qualitative is dominantly used. In collecting the data, the instruments used were questionnaire, observation sheet, and interview guide. The results show that both of teachers have a positive perception toward the PCK of teaching English to young learners. However, from the observation data, it is found that both teachers have a very low frequency in implementing the three components of PCK. Moreover, it was revealed that there was lack of consistency between the teachers’ perceptions and the implementation of PCK. Since, there was lack of consistency between the teachers’ perceptions and their implementation of Pedagogical Content Knowledge (PCK) in teaching English for young learners in Gianyar, it is suggested for the teachers to enhance their knowledge about PCK of teaching English to young learners and also enhance their teaching skills by attending seminars or workshops related to teaching English to young learners